PENGEMBANGAN ALAT UKUR COMPRESSION TESTER - Wilantara, Bahtiar; Raharjo, Raharjo (Jurnal E-Komtek (Elektro-Komputer-Teknik), 2019)
This study aims to develop an analog compression tester measuring instrument into a digital compression tester as a measurement tool that can provide effectiveness and efficiency to users. This research is a research and development or R&D. This research was conducted in several steps, namely: problem identification, information gathering, product design, product manufacture, expert validation, product revision, testing, final production. The development of analog compression tester was first validated by material experts, media experts, and 15 students, and 5 students for field trials. The subjects of this study were vocational students at Taman Karya Madya Teknik Kebumen. Data collection techniques used in this study using instruments in the form of a questionnaire. The data analysis technique of this research is descriptive qualitative and quantitative descriptive percentage. The results of the development of digital compression tester designs are: 1) the tools and materials used are electric drill, grinding, cutter, goggles, gloves, masks, ruler, acetaminine welding, screwdriver, scissors, digital dial pressure gauge, hose, spark plugs, clamps , and nepel, 2) the manufacturing process that starts from the cutting process, the hole drilling process, the welding process and the process of connecting between components, 3) the workings of digital compression tester design that is reading the pressure or compression of the machine displayed on the monitor digitally using dial pressure digital gauge, 4) the test results obtained from the validation results from: a) material experts at 89% or Eligible; b) media experts at 85% or reasonable; c) response of field trial students in terms of ease of use and reading of 90% or feasible. Thus, the conclusion that the digital compression tester measuring instrument declared feasible to use for measurement.